(untitled) (Revista Contexto & Saúde, 2025)
To associate dietary patterns with cardiometabolic markers in overweight and obese adolescents. A cross-sectional study was conducted with 227 adolescents aged 10 to 19 years, who were attending six public healthcare services in a city in Southern Brazil. A semi-quantitative food frequency questionnaire was administered. Dietary patterns were identified using principal component analysis followed by orthogonal Varimax rotation. Independent associations between dietary patterns and marker values (glucose, fasting insulin, Homeostatic Model Assessment index, total cholesterol, triacylglycerols, Low-Density Lipoprotein, High-Density Lipoprotein, cholesterol not transported by HDL, C-reactive protein, and blood pressure) were tested using quantile regression. The scores of dietary patterns were categorized into tertiles and associated with the outcomes of altered cholesterol transported by HDL or triacylglycerols levels due to their significant associations. A significance level of p<0.05 was considered. Five dietary patterns were identified: ‘Meat and eggs’, ‘Coffee, dairy, and vegetables’, ‘Breads and processed meats’, ‘Sugar and fat’, and ‘Soup and cereals’. The ‘Meat and eggs’ pattern, characterized by red meat, white meat, and eggs, was the most representative and showed a negative association with cholesterol transported by HDL and a positive association with triacylglycerols. The ‘Soup and cereals’ pattern had a positive association with triacylglycerols. Adolescents belonging to the third tertile of the ‘Meat and eggs’ pattern had 2.76 times higher odds of elevated triacylglycerols. Greater adherence to the ‘Meat and eggs’ pattern was associated with lower levels of cholesterol transported by HDL and higher plasma triacylglycerols.